Social representations of oncological patients' illness process under palliative care at home - Michele Rodrigues Matos; Rosani Manfrin Muniz; Michele Cristiene Nachtigall Barboza; Aline da Costa Viegas; Juliana Amaral Rockembach; Luiz Guilherme Lindemann (Universidade Federal de Santa Maria, 2017)
Aim: to know social representations of the process of becoming ill as an oncological patient under palliative care in the home context. Method: this is a qualitative, exploratory and descriptive study, which was developed with ten oncological patients under palliative care, from May to July 2015. Moscovici's Social Representations Theory and thematic analysis were used. Results: the process of becoming ill brings losses and restrictions in what concerns daily life and earning capacity. In order to cope with it, the support network comes from family, social network, spirituality, and health providers. There has been some modifications in what concerns social representations that associate cancer to death, with treatment evolution and improvement of cancer prognosis. Therefore, the participants felt hopeful about cure. Final considerations: It was observed that being sick with cancer in palliative care can influence negatively due to restrictions in daily life and in productive capacity; In addition to modifying the social representation that associates cancer with death and, regardless of the stage of the patients presence, they presented hope of healing, associated or not with the faith.